2017
DOI: 10.1007/s00248-017-0987-x
|View full text |Cite
|
Sign up to set email alerts
|

Shared Epizoic Taxa and Differences in Diatom Community Structure Between Green Turtles (Chelonia mydas) from Distant Habitats

Abstract: The first reports of diatoms growing on marine mammals date back to the early 1900s. However, only recently has direct evidence been provided for similar associations between diatoms and sea turtles. We present a comparison of diatom communities inhabiting carapaces of green turtles Chelonia mydas sampled at two remote sites located within the Indian (Iran) and Atlantic (Costa Rica) Ocean basins. Diatom observations and counts were carried out using scanning electron microscopy. Techniques involving critical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Moreover, the species composition of epibiotic diatoms from freshwater turtles of the same species can differ based on turtle activities and their region of origin [ 46 ]. Similar differences have been observed with marine turtles [ 27 ]. Nevertheless, such differences were not observed between freshwater turtles ( Emys orbicularis ) coming from various ponds in South France (e.g., [ 47 ]) nor for certain marine turtles ( Lepidochelys olivacea , [ 28 ]).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the species composition of epibiotic diatoms from freshwater turtles of the same species can differ based on turtle activities and their region of origin [ 46 ]. Similar differences have been observed with marine turtles [ 27 ]. Nevertheless, such differences were not observed between freshwater turtles ( Emys orbicularis ) coming from various ponds in South France (e.g., [ 47 ]) nor for certain marine turtles ( Lepidochelys olivacea , [ 28 ]).…”
Section: Introductionsupporting
confidence: 89%
“…Identification using light microscopy reaches its limits when small species are too abundant; therefore, microscopic counts introduce significant uncertainty. A large set of epibiotic diatoms samples from turtles were analyzed using scanning electron microscopy, thus bypassing this problem and enabling robust identification [ 27 ]. Nevertheless, scanning electron microscopy is expensive and cannot be undertaken routinely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed taxon richness is clearly higher than currently observed from any other sea turtle species sampled so far. Majewska et al [4] recorded only 21 taxa in 38 carapace samples from olive ridley sea turtles in Costa Rica whereas, in another study, Majewska et al [16] reported 26 taxa belonging to 20 genera in 76 carapace samples from green turtles in Costa Rica and Iran. It is possible that the applied sampling technique in the latter two studies (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Currently, it is still unclear to what degree the sea turtle diatom communities overlap with those encountered by the animals within their feeding, grooming or mating areas. While some diatom taxa seem to be well-adapted to the challenging conditions on the animal body surface and may constitute a key element of the pioneer epizoic communities, some other species may be able to attach to and thrive on the sea turtle skin or carapace only at the later stages of biofilm formation (Majewska et al, 2017b.…”
Section: Introductionmentioning
confidence: 99%